Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Pegawai Kantor Desa Pusaka Rakyat Bekasi - Tiara Pricilia; Sugeng Suroso; Ery Teguh Prasetyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to find out whether there is an influence of Work Training and Discipline on Employee Performance at the Bekasi People's Heritage Village office. The method used in this research is a quantitative method. The population in this study was 46 people. The sampling technique uses a non-probability sampling technique with a saturated sample method (census) where all members of the population are sampled. The data collection technique is by distributing questionnaires and processing them using the SPSS version 27 application. This research uses multiple linear regression analysis, and hypothesis testing using the t test and F test. The results of the research show that in the partial test (t) the training variable has an effect on employee performance with t count 3.537 > t-table 2.01669 and sig value. 0.001 < 0.05, the work discipline variable influences employee performance with a calculated t value of 6.176 > 2.01669 and a sig. 0.000 < 0.05, and the results of the simultaneous test (F) of the training and work discipline variables influence employee performance with a calculated F value of 27.738 > F-table 3.21 and sig.0.000 < 0.05.